Intraoperative Hypotension and Myocardial Infarction Development Among High-Risk Patients Undergoing Noncardiac Surgery: A Nested Case-Control Study. (July 2021) - Hallqvist, Linn; Granath, Fredrik; Fored, Michael; Bell, Max
Abstract : BACKGROUND: Hemodynamic instability during anesthesia and surgery is common and associated with cardiac morbidity and mortality. Information is needed regarding optimal blood pressure (BP) threshold in the perioperative period. Therefore, the effect of intraoperative hypotension (IOH) on risk of perioperative myocardial infarction (MI) was explored. METHODS: A nested case-control study with patients developing MI <30 days postsurgery matched with non–MI patients, sampled from a large surgery cohort. Study participants were adults undergoing noncardiac surgery at 3 university hospitals in Sweden, 2007–2014. Matching criteria were age, sex, American Society of Anesthesiologists (ASA) physical status, cardiovascular disease, hospital, year-, type-, and extent of surgery. Medical records were reviewed to validate MI diagnoses and retrieve information on comorbid history, baseline BP, laboratory and intraoperative data. Main exposure was IOH, defined as a decrease in systolic blood pressure (SBP), in mm Hg, from preoperative individual resting baseline lasting at least 5 minutes. Outcomes were acute MI, fulfilling the universal criteria, subclassified as type 1 and 2, occurring within 30 days and mortality beyond 30 days among case and control patients. Conditional logistic regression assessed the association between IOH, decrease in SBP from individual baseline, and perioperative MI. Mortality rates were estimated using Cox proportional hazards. Relative risk estimates are reported as are the corresponding absolute risks derived from the well-characterized source population. RESULTS: A total of 326 cases met the inclusion criteria and were successfully matched with 326 controls. The distribution of MI type was 59 (18%) type 1 and 267 (82%) type 2. Median time to MI diagnosis was 2 days; 75% were detected within a week of surgery. Multivariable analysis acknowledged IOH as an independent risk factor of perioperative MI. IOH, with reduction of 41–50 mm Hg, from individual baseline SBP, was associated with a more than tripled increased odds, odds ratio (OR) = 3.42 (95% confidence interval [CI], 1.13-10.3), and a hypotensive event >50 mm Hg with considerably increased odds in respect to MI risk, OR = 22.6, (95% CI, 7.69-66.2). In patients with a very high-risk burden, the absolute risk of an MI diagnosis increased from 3.6 to 68 per 1000 surgeries. CONCLUSIONS: In patients undergoing noncardiac surgery, IOH is a possible contributor to clinically significant perioperative MI. The high absolute MI risk associated with IOH, among a growing population of patients with a high-risk burden, suggests that increased vigilance of BP control in these patients may be beneficial.